Coronavirus Components and Execution Phase of Higher Education and Institutional Advancement Project in Rwanda: A Case of Ur-Sweden Programme for Research, Higher Education, and Institutional Advancement - Edwige, Isimbi; Irechukwu, Eugenia Nkechi (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
Project execution is a phase in which resources get allocated to deliver outcomes expected by stakeholders, while bringing to reality the vision of the project. Many projects often fail during execution phase due to failure to meet beneficiaries’ needs, due to different knowns or unknowns. Coronavirus is one of the unknowns that might have affected projects’ execution phase in one way or another. So, the main intention of this study is to determine the effect of coronavirus components on project execution phase: a case study of UR-Sweden programme for research, higher education, and institutional advancement. In this research, a census has been employed to collect quantitative data from respondents by use of Likert scale questionnaires. From 41 questionnaires distributed only 37 respondents filled them, representing a 90.2% response rate. To analyze the quantitative data, a descriptive and inferential research design were done using SPSS version 20.0. From the findings, there is a negative correlation of -0.384 between lockdown and project execution phase, a negative correlation between physical distancing and project execution phase of -0.329, and a negative correlation between curfew and project execution phase of -0.301. From the multiple regression analysis, it was found that: a change in lockdown by one unit leads to 0.366 decrease in the project execution phase, a change in curfew by one unit leads to a 0.130 decrease in the project execution phase, and a unit change in physical distancing leads to a 0.489 decrease in the project execution phase. In addition, from the hypothesis testing done at a significance level of 5%, it is clear that the relationship between lockdown and project execution phase is statistically significant, as well as the relationship between physical distancing and project execution phase. However, the relationship between curfew and project execution phase is not statistically significant.